Dietary L-glutamate modulates intestinal mucosal immunity of juvenile hybrid striped bass (Morone saxatilis ♀ × Morone chrysops ♂) - Hissen, Karina L.; He, Wenliang; Wu, Guoyao; Criscitiello, Michael F. (Frontiers in Immunology, 2025)
IntroductionL-Glutamate is a conditionally essential amino acid, meaning it can become essential under specific conditions, like stress or disease. It is an abundant intracellular amino acid crucial in immune responses. Supplementation of feed with key amino acids, such as glutamate, can optimize growth and have other health benefits for production animals. Most research on dietary amino acid supplementation has focused on mammalian models, thus this research turned to hybrid striped bass, a teleost fish of growing importance to the aquaculture industry. The study investigated the effects of dietary supplementation with 0% or 5% glutamate in hybrid striped bass on intestinal mucosal immunity. MethodsThe basal purified diet contained crystalline amino acids, including 3% L-glutamate. After an 8-week period of dietary supplementation with 5% glutamate followed by lipopolysaccharide stimulation, the intestinal mucosa was analyzed at the cellular and molecular levels to compare with the head kidney to assess potential changes in immune reactivity.ResultsOne week after lipopolysaccharide stimulation, glutamate supplementation enhanced (P < 0.05) the whole-body growth of fish without lipopolysaccharide challenge, total respiratory burst (the sum of O2– and H2O2 production) in head kidney leukocytes, the net production of H2O2 in intestinal mucosal leukocytes, and upregulation of expression of mRNAs for IL-1β, TNF-α, and IgT in the gut mucosa. DiscussionDietary supplementation with 5% L-glutamate may modulate intestinal mucosal immunity and improve growth in HSB to enhance disease resistance. Further research is needed to clarify the mechanism and cost-effective application.